2004
DOI: 10.1161/01.cir.0000140265.21608.8e
|View full text |Cite
|
Sign up to set email alerts
|

Antiinflammatory Effects of Angiotensin II Subtype 1 Receptor Blockade in Hypertensive Patients With Microinflammation

Abstract: Background-Experimental studies revealed proinflammatory properties of angiotensin II. We evaluated antiinflammatory effects of the angiotensin II subtype 1 receptor antagonist olmesartan medoxomil alone and in cotherapy with the HMG-CoA reductase inhibitor pravastatin in patients with essential hypertension and microinflammation. Methods and Results-We measured a panel of vascular inflammation markers, including high-sensitivity C-reactive protein, and lipid levels during 12 weeks of therapy with olmesartan (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
170
2
7

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 376 publications
(188 citation statements)
references
References 44 publications
9
170
2
7
Order By: Relevance
“…Serum levels of hsCRP, an anti-inflammatory marker, were significantly decreased by olmesartan, but not amlodipine, an observation consistent with a previous study. 25 As additional confirmation of the anti-inflammatory property of olmesartan, we measured urine monocyte chemoattractant protein-1 levels finding that, though not statistically significant, olmesartan tended to decrease urine monocyte chemoattractant protein-1 levels. Regarding EC-SOD, an antioxidative property of the vasculature, neither pre-nor post-EC-SOD levels, or the resulting heparin-releasable EC-SOD levels were changed by either treatment.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Serum levels of hsCRP, an anti-inflammatory marker, were significantly decreased by olmesartan, but not amlodipine, an observation consistent with a previous study. 25 As additional confirmation of the anti-inflammatory property of olmesartan, we measured urine monocyte chemoattractant protein-1 levels finding that, though not statistically significant, olmesartan tended to decrease urine monocyte chemoattractant protein-1 levels. Regarding EC-SOD, an antioxidative property of the vasculature, neither pre-nor post-EC-SOD levels, or the resulting heparin-releasable EC-SOD levels were changed by either treatment.…”
Section: Resultsmentioning
confidence: 86%
“…The present study demonstrated that olmesartan significantly reduced serum hsCRP levels as previously reported. 25,[45][46][47] However, the changes in hsCRP levels were not associated with those in FMD. As in the case of microalbuminuria, as RAS inhibition produces pleiotropic effects, there may not be a simple one-to-one correlation between serum hsCRP levels and endothelial function either.…”
Section: Discussionmentioning
confidence: 90%
“…We have recently demonstrated that inflammatory urine biomarkers also increase in response to acute clamped hyperglycaemia; however, the role of the RAAS in mediating this response and the reversibility of this phenomenon was unknown. We hypothesised that blockade of the RAAS would mitigate the effect of clamped hyperglycaemia on urinary cytokines/chemokines [37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…22 Assuming a CV of 30%, it was determined that 100 completed patients (50 per group) would provide 90% power to detect a 20% difference between patient groups, whereas a CV of 50% would provide 50% power to detect the same change.…”
Section: Discussionmentioning
confidence: 99%